On the use of abiotic sialic acids to attenuate cell inflammation. Issue 1 (December 2018) - Xue, Zhongwei; Zhao, Hu; Zhu, Rui; Chen, Congcong; Cao, Hongzhi; Han, Jiahuai; Han, Shoufa
Abstract Sialic acid (Sia) residues on cell surface are critical for myriad cellular events such as immunity and inflammation. We herein reported the use of abiotic Sia to raise the thresholds of inflammatory cell responses. Identified from a panel of structurally diversified Sia analogs via a cell inflammation assay, Sia-2, withN -butyryl moiety at C-5, markedly lowered LPS-stimulated NF-κB activity in macrophages. Further analysis shows that Sia-2 attenuates phosphorylation of IκB and Erk1/2/p38/JNK, critical for NF-κB signaling and MAPK signaling, and lowers gene transcription of proinflammatory interleukin-6. These results support the use of abiotic Sia as promising agents to modulate cell surface Sia-pertinent cell signaling.